ELECTRONIC GOVERNMENT : SUATU INOVASI PENINGKATAN MANAJEMEN PUBLIK DALAM KERANGKA GOOD GOVERNANCE - Ipah Ema Jumiati (Jurnal Administrasi Publik, 2010)
Information technology era began in developed countries, where there is utilization of digital technology (Digital Electronic Services) has produced a form of government bureaucracy a new mechanism, known by the term Electronic Government (e-Government). With e-Government is expected interactions between the government and its people are too bureaucratic, the mechanism of interaction is much more friendly. In other words the implementation of e-Government is an orientation of new digital technologies in the development of management information systems as a result of the utilization of information technology developments and breakthroughs in order to service to the community faster, easier, cheaper without the limitation of space and time. In principle, the e-government is one way of providing public services more effective, efficient, transparent and accountable in line with the principles contained in the good governance (good governance). In the development and implementation in both developed countries and in developing countries, so far, e-government brings a positive impact on the application of these principles around the concept of good governance and public service. Therefore the application of e-government, which must be accompanied by reforms of public sector management, good corporate governance reform and strengthening of civil society is a thing that can not be put off no longer.